2014
DOI: 10.1016/j.yfrne.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of fetal hormonal programming (prenatal stress) implicates shared risk for sex differences in depression and cardiovascular disease

Abstract: Comorbidity of major depressive disorder (MDD) and cardiovascular disease (CVD) represents the fourth leading cause of morbidity and mortality worldwide, and women have a two times greater risk than men. Thus understanding the pathophysiology has widespread implications for attenuation and prevention of disease burden. We suggest that sex-dependent MDD-CVD comorbidity may result from alterations in fetal programming consequent to the prenatal maternal environments that produce excess glucocorticoids, which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 405 publications
1
67
0
2
Order By: Relevance
“…In fact, 17 unique collagen genes were down-regulated in the multi-miR-injected group PVN compared with controls. These findings may reflect deficits in cerebral circulation and/or blood-brain barrier permeability in the PVN, effects that would have significant impact on neuroendocrine function (36,37). Furthermore, the PVN is one of the most highly vascularized regions in the brain, suggesting that it may be particularly susceptible to developmental changes in circulation or permeability (38).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 17 unique collagen genes were down-regulated in the multi-miR-injected group PVN compared with controls. These findings may reflect deficits in cerebral circulation and/or blood-brain barrier permeability in the PVN, effects that would have significant impact on neuroendocrine function (36,37). Furthermore, the PVN is one of the most highly vascularized regions in the brain, suggesting that it may be particularly susceptible to developmental changes in circulation or permeability (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although deficits in HPA axis function are a hallmark of MDD (Gibbons and McHugh, 1962;Carroll et al, 1976a, b;Nemeroff et al, 1984;Arborelius et al, 1999;Webster et al, 2002;Parker et al, 2003;Holsen et al, 2013), gonadal hormone deficits are also evident Schmidt, 1996, 2006;Young et al, 2000Young et al, , 2007Himelein and Thatcher, 2006;Young and Korszun, 2002;Graziottin and Serafini, 2009; for a review, see Goldstein et al, 2014). For example, women with persistent MDD have twice the risk of early perimenopausal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian hormones modulate brain neurochemistry, structure, and function (Shanmugan and Epperson, 2014;Hantsoo and Epperson, 2015). (e) Prenatal stress contributes to risk for diseases that exhibit sex differences across the life span (Goldstein et al, 2014). (f) Mid-life is associated with marked hormonal shifts for women, but not men.…”
Section: Sex Differences Related To Sex Chromosomes and Hormones And mentioning
confidence: 99%
“…Certainly, one can get to the same destination via different routes. For instance, in neuropsychiatric diseases such as autism, schizophrenia, or depression, although men and women may be given a similar diagnosis, there exist significant sex differences in overall rates, timing of onset, symptom presentation, and treatment efficacy (Heim and Nemeroff, 1999;Heim and Nemeroff, 2001;Sanchez et al, 2001;Goldstein et al, 2002;Heim et al, 2004;Bale, 2006;Brown and Susser, 2008;Bale, 2009;Brown et al, 2009;Heim et al, 2009;Bale et al, 2010;Heim et al, 2010;Brown, 2012;Davis and Pfaff, 2014;Goldstein et al, 2014). Further, mechanistic animal studies modeling endophenotypes of these disorders have demonstrated robust sex differences in the timing of susceptibility to insults to the developing brain where males appear more vulnerable prenatally and females postnatally (Mueller and Bale, 2006;Mueller and Bale, 2007;Ivy et al, 2008;Kapoor et al, 2008;Mueller and Bale, 2008;Kapoor et al, 2009;Ivy et al, 2010;Hsiao and Patterson, 2012).…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 99%